ANALYSIS OF OCCUPATIONAL SAFETY AND HEALTH RISK MANAGEMENT ON THE INDONESIAN NAVY SHIP PROJECT USING HAZARD IDENTIFICATION, RISK ASSESSMENT AND RISK CONTROL - Sukmo Hadi Nugroho; Bambang Suharjo; Adi Bandono; Agus Tri Haryanto (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2020)
Indonesian Navy ships (KAL) is one element of the Integrated Fleet Weapon System (SSAT), which plays an important role in carrying out tasks in the defense field. So, we need an optimal KAL readiness to support the passage of the operation to be carried out successfully and smoothly. One of the ways used to prepare KAL is to carry out routine maintenance through the docking process. However, in practice there are accidents suffered by workers.This research was conducted using the HIRARC method. HIRARC is a method of hazard identification, risk assessment and risk control measures that are used for this method is considered moreappropriate and more accurately where the dangers that arise in the process described docking of any work activity. In this method also provides appropriate control measures for each hazard. Based on the results of the HIRARC analysis, each suction work activity of docking based Risk Ranking will be sorted according to the level of Risk Matrix and will be discussed further against high risks and implemented controls. Then the resulting draft recommendation to minimize workplace accidents in the docking process is by way of elimination, Administration Control and Use of PPE (Personal Protective Equipment).Keywords: HIRARC method, Docking process, KAL.